O COOPBRASS como iniciativa de descolonização em rede: desafios ao enfrentamento da violência epistêmica nas cooperações científicas do eixo sul-sul - Muniz, Claudia Maria Serino Lacerda (2024)
In this thesis I discuss the naturalized situations of internal colonialism and coloniality of knowledge, within the scope of the Scientific-Strategic Cooperation Program with the Global South (COOPBRASS), indicating the inherent contradictions that refer to the power patterns of the Global North. Specifically, I problematize the institution of Anglophony as the center of the scientific system and the influence of English, as the main language of science, in this context, discussing the implications of this monolingualism for the COOPBRASS scientific community. In this sense, I point to the need to consolidate Plurilingualism Policies for Southern Sciences (PLURICIS), which enable the production and circulation of knowledge in the various languages of the region – especially in the context of Latin America and the Caribbean, where research is based. driven. At the same time, discourse on the importance of legitimizing southern scientific journals for the visibility of knowledge produced in the Global South, as a way of confronting the epistemic violence that continues to be exercised in the territory. In the end, without detracting from the potential of COOPBRASS – to exchange Southern resources, knowledge and technologies – I present a test of alternatives to the contradictions listed in the Program, especially with regard to the criteria for selecting research proposals. Thus, based on the perspective of “Buen Vivir”, I conclude by suggesting a new research agenda for COOPBRASS, which can be thought of from the peripheries and with the necessary boldness to give new meaning to South-South Cooperation and the very ideas of integration, modernity and development.